Efforts to Reform Islamic Law: An Analytical of Muhammad Abduh's Thought - Ilham Kuncahyo; Muhammad Azis; Nur Kholis Aryanto; Anastasia Cahaya Utami; Urfa Faizah (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This research explores the role of tasyri' during the era of imitation and decline and the period of tasyri renewal. In this context, taser serves as a key to understanding the dynamics of change within Islamic legal frameworks. During the era of imitation, an in-depth examination was conducted on how taser was implemented and potentially distorted in practice. The focus then shifts to the decline period, identifying factors contributing to deviations from tasyri's principles. Subsequently, the research scrutinizes the era of easy renewal, tracing efforts to restore the integrity and relevance of Syria in the context of the modern age. The findings of this research provide profound insights into the evolution of tasyri' and its contribution to social and legal changes in Islamic history